Telework during the Pandemic: Patterns, Challenges, and Opportunities for People with Disabilities - Mason Ameri; Douglas L. Kruse; So Ri Park; Yana van der Meulen Rodgers; Lisa Schur (Institute of Labor Economics (IZA), 2022)
Telework has benefits for many people with disabilities. The pandemic may create new employment opportunities for people with disabilities by increasing employer acceptance of telework, but this crucially depends on the occupational structure. We compare people with and without disabilities in the expansion of telework as the pandemic began, and the evolution of telework during the pandemic. We use U.S. data from the American Community Survey from 2008 to 2020 and the Current Population Survey over the May 2020 to April 2022 period. Prevalence and trends are analyzed using linear probability and multinomial logit regressions. While workers with disabilities were more likely than those without disabilities to telework before the pandemic, they were less likely to telework during the pandemic. The occupational distribution accounts for most of this difference. Tight labor markets, as measured by state unemployment rates, particularly favor people with disabilities obtaining telework jobs. While people with cognitive/mental health and mobility impairments were the most likely to telework during the pandemic, tight labor markets especially favored the expansion of telework for people with vision impairments and difficulty with daily activities inside the home. Many people with disabilities benefit from working at home, and the pandemic has increased employer acceptance of telework, but the current occupational distribution limits this potential. Tighter labor markets during the recovery offer hope that employers will increasingly hire people with disabilities in both telework and non-telework jobs. Disability, employment, telework, pandemic, flexibility.
Keywords: J14; J22; J71; 330; disability; employment; telework; COVID-19; flexibility